Impact of inclusive leadership on innovative work behavior: The mediating role of job crafting - Yinping Guo; Junge Jin; Sang-Hyuk Yim (Administrative Sciences, 2023)
The study aims to examine the mediating role of job crafting between inclusive leadership and innovative work behavior. The data were collected from 314 workers employed in China's small and medium-sized industries. The data collection was done through survey design. The data analysis was done using Spss 26.0 and through structural equation modeling by Mplus 8. Inclusive leadership was found to be related to job crafting and innovative work behavior of the employees. Job crafting was found to be mediating between inclusive leadership and innovative work behavior. The study delineated the link mechanism between inclusive leadership and innovative work behavior. Studying inclusive leadership in the context of Chinese culture is a powerful complement to inclusive leadership theory. This paper provides the managers of SMEs with significant managerial insights into how inclusive leadership can effectively motivate employees' innovative work behaviors.
Keywords: 350; belongingness; inclusive leadership; innovative work behavior; job crafting; uniqueness